SV40 replication in human mesothelial cells induces HGF/Met receptor activation: A model for viral-related carcinogenesis of human malignant mesothelioma - Cacciotti, Paola (The National Academy of Sciences, 2001)
Recent studies suggested that simian virus 40 (SV40) may cause malignant mesothelioma, although the pathogenic mechanism is unclear. We found that in SV40-positive malignant mesothelioma cells, the hepatocyte growth factor (HGF) receptor (Met) was activated. In human mesothelial cells (HMC) transfected with full-length SV40 DNA (SV40-HMC), Met receptor activation was associated with S-phase entry, acquisition of a fibroblastoid morphology, and the assembly of viral particles. Coculture experiments revealed the ability of SV40-HMC to infect permissive monkey cells (CV-1), HMC, and murine BNL CL cells. Cocultured human and murine SV40-positive cells expressed HGF, showed Met tyrosine phosphorylation and S-phase entry, and acquired a spindle-shaped morphology (spBNL), whereas CV-1 cells were lysed. Cocultured HMC inherited from SV40-HMC the infectivity, as they induced lysis in cocultured CV-1 cells. Treatment with suramin or HGF-blocking antibodies inhibited Met tyrosine phosphorylation in all large T antigen (Tag)-positive cells and reverted the spindle-shaped morphology of spBNL. This finding indicated that Met activation and subsequent biological effects were mediated by an autocrine HGF circuit. This, in turn, was causally related to Tag expression, being induced by transfection with the SV40 early region alone. Our findings suggest that when SV40 infects HMC it causes Met activation via an autocrine loop. Furthermore, SV40 replicates in HMC and infects the adjacent HMC, inducing an HGF-dependent Met activation and cell-cycle progression into S phase. This may explain how a limited number of SV40-positive cells may be sufficient to direct noninfected HMC toward malignant transformation.